Microbiome-Metabolome Responses to a High-Grain Diet Associated with the Hind-Gut Health of Goats - Tao, Shiyu; Tian, Ping; Luo, Yanwen; Tian, Jing; Hua, Canfeng; Geng, Yali; Cong, Rihua; Ni, Yingdong; Zhao, Ruqian (Frontiers in Microbiology, 2017)
Studies on the effect of a high-concentrate (HC) diet on the hindgut microbiota and metabolome of ruminants are rarely reported. We used 454 pyrosequencing of 16S rDNA genes and gas chromatography-mass spectrometry to evaluate the effects of long-term feeding (HL) or short-term (HS) feeding of an HC diet on changes in bacterial microbiota and their metabolites in the hindgut, with Guanzhong goat as a ruminant model. Results indicated that an HC diet decreased bacterial diversity and induced metabolic disorder in the hindgut. The levels of lactate, endotoxin (lipopolysaccharide, LPS), and volatile fatty acid concentrations were higher in the intestinal digesta of the HC goats than in those of the LC goats (P < 0.05). The level of beta-alanine decreased, whereas the levels of stigmasterol and quinic acid decreased in the cecal and colonic digesta of the HC goats. At the genus level, the abundance of Clostridium and Turicibacter was significantly increased in both the colonic and cecal digesta of the HC goats. Several potential relationships between metabolites and several microbial species were revealed in this study. The mRNA expression of the genes functionally associated with nutrients transport, including NHE2, NHE3, MCT1, and MCT4 were significantly downregulated in the colonic mucosa by the HC diet (P < 0.05). The expression levels of the genes related to the inflammatory response, including TLR4, MYD88, TNF-α, and IL-1β were markedly upregulated in the cecal mucosa by the HC diet (P < 0.05). Our results indicate that an HC diet induces microbiota dysbiosis, metabolic disorders, and mucosal damage in the hindgut of goats.